Duplex-Repair enables highly accurate sequencing, despite DNA damage. Issue 1 (30th September 2021) - Xiong, Kan; Shea, Douglas; Rhoades, Justin; Blewett, Timothy; Liu, Ruolin; Bae, Jin H; Nguyen, Erica; Makrigiorgos, G Mike; Golub, Todd R; Adalsteinsson, Viktor A
Abstract: Accurate DNA sequencing is crucial in biomedicine. Underlying the most accurate methods is the assumption that a mutation is true if altered bases are present on both strands of the DNA duplex. We now show that this assumption can be wrong. We establish that current methods to prepare DNA for sequencing, via 'End Repair/dA-Tailing, ' may substantially resynthesize strands, leading amplifiable lesions or alterations on one strand to become indiscernible from true mutations on both strands. Indeed, we discovered that 7–17% and 32–57% of interior 'duplex base pairs' from cell-free DNA and formalin-fixed tumor biopsies, respectively, could be resynthesized in vitro and potentially introduce false mutations. To address this, we present Duplex-Repair, and show that it limits interior duplex base pair resynthesis by 8- to 464-fold, rescues the impact of induced DNA damage, and affords up to 8.9-fold more accurate duplex sequencing. Our study uncovers a major Achilles' heel in sequencing and offers a solution to restore high accuracy.